2022
DOI: 10.1007/s00428-021-03262-8
|View full text |Cite
|
Sign up to set email alerts
|

Variable levels of spike and ORF1ab RNA in post-mortem lung samples of SARS-CoV-2-positive subjects: comparison between ISH and RT-PCR

Abstract: Post-mortem examination plays a pivotal role in understanding the pathobiology of the SARS-CoV-2; thus, the optimization of virus detection on the post-mortem formalin-fixed paraffin-embedded (FFPE) tissue is needed. Different techniques are available for the identification of the SARS-CoV-2, including reverse transcription polymerase chain reaction (RT-PCR), immunohistochemistry (IHC), in situ hybridization (ISH), and electron microscopy. The main goal of this study is to compare ISH versus RT-PCR to detect S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…All patients who died from a lethal form of SARS-CoV-2 infection in our cohort of COVID-19 lethal disease had ARDS due to lung tissue viral persistence demonstrated by PCR as previously reported [32]. Therefore in this study we presented the percentage of Spike-1 (+) cases as evaluated by ISH compared to mean values ± Standard Error Means (SEM) of selected studied markers (TLR-4, CD68, CD163, GAL-3) (Table 1 and Figure 2).…”
Section: In Situ Hybridization (Ish)supporting
confidence: 66%
See 1 more Smart Citation
“…All patients who died from a lethal form of SARS-CoV-2 infection in our cohort of COVID-19 lethal disease had ARDS due to lung tissue viral persistence demonstrated by PCR as previously reported [32]. Therefore in this study we presented the percentage of Spike-1 (+) cases as evaluated by ISH compared to mean values ± Standard Error Means (SEM) of selected studied markers (TLR-4, CD68, CD163, GAL-3) (Table 1 and Figure 2).…”
Section: In Situ Hybridization (Ish)supporting
confidence: 66%
“…Briefly, ISH detection of SARS-CoV-2 was been performed using V-nCoV2019-S probe to detect viral sequences Spike (S) of SARS-CoV-2 in lung tissue using RNAscope 2.5 high-definition detection kit (Advanced Cell Diagnostics). SARS-CoV-2 was been detected in lung tissues of lethal COVID-19 disease by in ISH according to methods reported in previous work of our laboratories in which we compared ISH with PCR methods [32,56,57], and in current literature [58,59].…”
Section: In Situ Hybridization (Ish) Methods For Sars-cov-2 Detectionmentioning
confidence: 99%
“…4 ) and inhibits SARS-CoV-2 replication as measured by its inhibition of mRNA expression of two different SARS-CoV-2 genes, spike (S) and open reading frame (ORF1b) ( Fig. 5 A and B) [ 50 ]. Different studies were conducted to gain more insight into the viral inhibitory mechanism of SIMR3030.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 24 RNAscope probes for negative-sense spike RNA were applied in several studies and visualisation of intracellular puncta was reported in some of these studies, but without correlation with the disease course ( Table S1 ). 19 , 20 , 22 , 25 , 26 Visualisation of positive-sense intracellular RNA species 10 , 11 , 13 , 14 , 19 , 25 , 26 , 27 , 28 , 29 or nucleocapsid/spike-immunoreactive signal 10 , 12 , 13 , 14 , 15 , 23 , 26 , 30 , 31 , 32 , 33 has frequently been proposed to identify target cell types of SARS-CoV-2 in the lung ( Table S1 ) but does not provide robust evidence about cell tropism and ongoing viral replication. 23 , 31 , 34 …”
Section: Discussionmentioning
confidence: 99%